(The Effect of Oleoresin Concentration Level and Material Compositions for Encapsulating on the Properties of Microencapsulated Pepper Oleoresin by Using Spray Drying) - Sudibyo, Agus; P. Simanjuntak, Helmud (Warta Industri Hasil Pertanian, 2009)
Research one of black pepper oleoresin concentration and encapsulating material kompositions on the properties of microencapsulated pepper oleoresin has been conducted. oleoresin was extracted from dried black pepper with ethanol using percolation technique and it was encapsulated in maltodextrinÂ  and sodium caseinate using spray equipment. Experiments were performed using complete randomized factorial experimental desige whit two factrs. Factor A oleoresin concentration; i.e A1 = 10%, A2 = 15% and A3 29% and factor B are maltodextrin to sodium caseainate ratio, i.e. B1 = 90 : 10 and B2 = 75 : 25. then yield, volatile oil retention, piperine content were evaluated. It was found that higher solid concertration will increase the retention of volatile oil and piperine content. The best microcapsule properties was obtained from microcapsules product containing oleoresin 10% and malto-dextrin and sodium caseinate at the ratio of 75 : 25 white the yield of 68.75%, volatile of 2.25%, piperine content of 3.215 and moisture content of 3.75%.